Reactivation of UV-Irradiated Adenovirus Type 2 and Herpes Simplex Virus Type 1 in Mammalian Cells - Bueschleb, Ann (My University, 1987)
Much research is being conducted into the causes of human cancer. A number of human autosomal recessive diseases such as Xeroderma Pigmentosum are characterized at least in part by a defect or aberration in one or more forms of DNA repair and at the same time an elevated incidence of cancer. Also, carcinogens cause mutations in DNA and the greater the carcinogenicity, the greater the mutagenicity. As a result, much attention has been focused on DNA repair and its relationship to cancer incidence. The HCR of V antigen formation by UV-irradiated Adenovirus type 2 (Ad 2) was examined using apparently normal human fibroblasts, tumor cells (HeLa CCL2), and cells transformed by Ad 5 DNA (293, 293 N3S). A decrease in the HCR of V antigen formation was found for HeLa CCL2 cells as compared to apparently normal human fibroblasts, but not for the transformed cells. These results are discussed in terms of the characteristics of the cell types. Herpes simplex virus type I encodes a polymerase and thymidine kinase (tk) activity which are involved in viral DNA synthesis. Paa ᷇ 5, an HSV-1 mutant containing one or more mutations in the polymerase gene is an antimutator. If these are also involved in viral DNA repair, then the HSV-1 polymerase, tk activity, and mutant polymerases conferring altered mutation rates should provide excellent tools with which to probe cellular DNA repair processes and mutagenesis. The study of the HCR of plaque forming ability of HSV-1 KOS wild type (WT), Paa ᷇ 5 and PTK3B (lacking thymidine kinase activity ) using VERO cells revealed a decrease in the HCR of Paa ᷇ 5 and increase of surviving fractions of PTK3B with respect to that of HSV-1 KOS WT. Similar studies using apparently normal human fibroblasts, Xeroderma Pigmentosum and Cockayne Syndrome cells also implicated the HSV-1 polymerase in viral DNA repair. The results are discussed in terms of the function of the HSV-1 polymerase and the DNA repair abilities of XP and CS cells.
Reactivation of UV-Irradiated AD 2 and HSV-I in Mammalian Cells
Keywords: UV radiation; adenovirus type 2; herpes simplex type 1; mammal; cancer